Letter from John Jennings, Munster Furnishing Co., to Michael Collins, INAAVD, regarding the Cork annual meeting, and asking for lists of subscribers from Cork County - Jennings, John, Draper; Collins, Michael, 1890-1922; Irish National Aid and Volunteers' Dependants' Fund (1917)
Letter also sends subscription money, not extant.
Inscribed on headed paper "The Munster Furnishing Co. / John Jennings, Proprietor. / Upholsterers and Bedding Manufacturers. / 11, Great George's Street, Cork,".
Keywords: Ireland -- History -- 1910-1921